Role of Gender Diversity on Corporate Social Responsibility: Evidence from a Developing Economy - Chandula A M T; Dissanayake H; Anuradha I. (International Journal of Academe and Industry Research, 2023)
While the importance of Corporate Social Responsibility (CSR) increased during the COVID-19 period, it is also imperative to increase the female representation of the board. Empirical evidence suggests inconclusiveness of the results in the country, period and methods applied. In addition, there is a dearth of studies in the world as well as developing economies. To bridge these research gaps, this study examined the impact of gender diversity on corporate social responsibility in the developing economy as Sri Lanka during the COVID-19 period. A quantitative study using a survey design was conducted with sample size of 133 companies listed at Colombo Stock Exchange using random sampling. The data analysis included descriptive analysis and correlation using Statistical Package for Social Science (SPSS) and Partial Least Squares Regression Model through SMART PLS 3.0. This study found the level of gender diversity in Sri Lanka is 10% indicating low level in the developing economy. Findings also revealed that gender diversity and legal responsibility have significant impact while economic, ethical, and philanthropic have no impact on Sri Lankan companies. Although the study is limited to listed companies and quantitative cross-sectional study, results clearly suggest an increase to the percentage of women directors on board to improve legal responsibility and further achieve sustainable goals in the economy. The findings also suggest new perspective on resource dependence theory.